Heidegger's fenomenology -from Husserl to Heidegger - Hoyos, Jaime (Estudios de Filosofía, 1991)
The recent edition of the Marburg Lectores (1923-1928) once again clarifies the position of Being and Time in Heidegger's works. Through a minute comparison of Husserl's Transcendental Phenomenology and Heidegger's Ontological Phenomenology, the author shows the latter's persistence in phenomenology as raison d'étre of his most authentic originality, as well as of his having overcome the metaphysics of subjectivity, the line of influence of which goes from Descartes to Husserl.